Impact of alcohol washing on the flavour profiles, functionality and protein quality of air classified pea protein enriched flour. (June 2020) - Wang, Yun; Guldiken, Burcu; Tulbek, Mehmet; House, James D.; Nickerson, Michael
Graphical abstract: Highlights: All treatments reduced the total volatile compounds, except 20% isopropanol. Increasing alcohol concentration increased the removal of volatile compounds. Alcohol washing increased water holding capacity, and decreased oil holding capacity. Colour change of alcohol treated samples decreased with increasing concentrations. Alcohol treatment decreased the solubility of pea protein flour. Abstract: In this study the potential of aqueous solvent washing on removing off-flavours in air classified pea protein-enriched flour (PPEF) was investigated. Unpleasant flavour compounds are one of the main deterrents to the application of pulses. PPEF was treated with ethanol or isopropanol at three different concentrations (20%, 50%, and 80%) to remove the volatiles related to unpleasant beany, earthy and astringent flavours. Headspace solid phase microextraction followed by GC-MS was used to identify the flavour compounds in untreated and treated PPEF. Besides the flavour profile, changes to their proximate composition, colour, functionality and protein quality were compared among untreated and treated samples. Higher concentrations of ethanol and isopropanol (50% and 80%) showed greater effectiveness in removing flavour compounds by reducing the total peak area by 82%–94%. Protein content in all treated samples (58.2%–64.3% d.b.) increased compared to untreated PPEF (55.5%) as a result of purification due to the decrease in ash, lipid and carbohydrate content. However, alcohol treatment reduced the protein solubility and oil holding capacity in all samples by 38.3%-75.9%, and 16.7%-30.2%, respectively. Although in vitro protein digestibility was improved with the solvent treatments, the amino acid scores of those samples became lower (i.e., reduced levels of methionine, cysteine or tryptophan) resulting in up to a 27.8% reduction in in vitro protein digestibility correct amino acid scores. Both ethanol and isopropanol at 50% and 80% concentration proved to be effective in removing flavour compounds in PPEF with some modifications on the chemical compositions, protein functionalities and quality.